IBM Z functional matrix - Lascu, Octavian; White, Bill (Telecommunications engineer); Palacio, Ewerson (IBM redbooks., 2022)
This IBM® Redpaper™ publication provides a list of features and functions that are supported on IBM Z. On 30 June 2021, the IBM z14 (M/T 3906) was withdrawn from marketing (WDMF). Field-installed features and all associated conversions that are delivered solely through a modification to the machine's Licensed Internal Code (LIC) are still possible until 29 June 2022. This IBM Redpaper publication can help you quickly understand the features, functions, and connectivity alternatives that are available when planning and designing IBM Z infrastructures.